Behavioral dividend policy - Marc Gürtler; Nora Hartmann (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2003)
In this paper we develop an optimal dividend policy in the presence of limited rational inves-tors. Concretely, investors with mental accounts for dividends and stock prices as well as emotions like disappointment and elation embody the limited rationality. Furthermore, investors evaluate changes in wealth instead of final wealth. A management maximizing investors' modified utility results in the optimality of dividend payments as well as dividend smoothing, which both have long been puz-zles to financial theorists. Moreover, a model specification leads to a gradual dividend adjustment to changes in net earnings as described by Lintner (1956).
Keywords: G35; 330; dividend policy; dividend smoothing; behavioral finance